Neuronal ceroid lipofuscinoses: many players, and more to come. (September 2009) - Simonati, Alessandro; Cannelli, Natalia; Pezzini, Francesco; Aiello, Chiara; Bianchi, Marzia; Tessa, Alessandra; Santorelli, Filippo M
The neuronal ceroid lipofuscinoses (NCL) are the most common group of progressive neurodegenerative diseases of childhood. The overall clinical features are highly similar regardless of the age at disease manifestation, the extent and shape of abnormally stored cytosomes and the severity of clinical course, and are generally characterized by failure and regression of psychomotor development, impaired vision, seizures and fatal outcome. The expanding array of genetic etiologies and disease-associated mutations in NCL provide the basis for the heterogeneity of these clinical conditions and are the focus of this review. Less understood are the pathogenic mechanisms, but common themes and molecular pathways are now emerging and new players are expected to come into the scene of NCL.